INFLUENCE OF THE SURFACE-ACTIVE COMPONENT OF COMPLEX MODIFIER ON THE STRUCTURE OF LOW-CARBON STEEL - O. S. Komarov; V. I. Volosatikov; D. O. Komarov (Литьë и металлургия)
The influence of surface-active component of complex modifier on structure of low-carbon steel is shown. It is determined that the complex modifier, containing carbideforming and surface-active components, influences more effectively on macro- and microstructure of low-carbon steel.